Comparative Study on TGF-β Expression of Large Continues and Small Continues Stitch Technique Using Polyglecaprone 25 on Abdominal Skin Incision in Rattus Novergicus - Dhyas Munandar AS (Universitas Ahmad Dahlan, 2021)
Ideal closing of the abdominal wound will provide strength and prevent infection. Abdominal wall closure method is an important aspect of effective incision closure, besides the choice of suture material. TGF-β generally involved in wound healing process. The suture technique is also important in wound healing process. This study aims to compare the large stitch technique with the small stitch technique for abdominal skin closure. Twenty rats were used in 4 groups. The small stitch group received small tissue bites of 5 mm from wound edge, and the large tissue group received large bites of 10 mm from wound edge. The incision of the skin was closed by running suture using polyglecarprone 25. Animal model were euthanized on the 4th and 7th day post incision. Tissue section were examined using immunohistochemistry method to measure TGF-β expression. The results were analyzed using t-test and the effect size. Rats in the small stitch group had higher TGF-β expression on day 4th and 7th than those in the large stitch group. TGF-β expressions in the small stitch group were 0,87 -fold greater on day 7th than day 4th and were 0,71 -fold greater in the large stitch group (p = 0,410). The significance analysis on day 4th with a result of 0,082 and day 7th with a result of 1.48, which means day 7th showed high effect (Cohen's d> 0.8) on wound healing than day 4th. In conclusion, polyglecaprone 25 use as a suture material on the day 7th showed a high effect in terms of TGF- β expression.